Survey on Transformational Leadership Models in Improving the Quality of Academic Services of Elementary Schools - Sunaengsih, Cucun; Djuanda, Dadan; Irawati, Riana; Isrok'atun, Isrok'atun; Karlina, Dety Amelia; Juneli, Juni Artha (Universitas Pendidikan Indonesia, 2023)
This study aims to identify how the transformational leadership model in improving the quality of academic services implemented in elementary schools. This study was conducted using survey methods and interviews with 50 elementary school teachers in Sumedang, West Java Province, Indonesia. This study aims to find out how implementing transformational leadership in elementary schools improves academic services across different dimensions, aiming to identify the average improvement. The findings indicated that the overall dimensions of the transformational leadership model were rated as good. These dimensions include idealized influence (charismatic), intellectual stimulation, individual consideration, and inspirational motivation. While not achieving a perfect score, it is anticipated that the average scores across these four dimensions of the transformational leadership model will significantly contribute to improving the quality of academic services in elementary schools.